溫補學派5人의 痰飮인식에 대한 연구 - 김진호(Jin Ho Kim); 박해모(Hae Mo Park) (동의생리병리학회지, 2012)
This study aimed to examine the recognition on phlegm-retained fluid of the Onbo School’s five physicians, Xue Ji(薛己), Sun Yi-kui(孫一奎), Zhao Xian-ke(趙獻可), Zhang Jie-bin(張介賓), and Li Zhong-zi(李中梓), who made important contributions in the formation of Tanbing theories. Five authors were included as the study subjects. The study examined on the definition, causes, classification, therapeutic methods, and instructions of phlegm-retained fluid. The results are 1. Phlegm-retained fluid is formed when the normal circulation of body fluid is not functioning properly. Plegm (痰) is thick, slimy, and murky fluid. In contrast, retained fluid(飮) is clear and watery fluid. 2. The major causal organs of phlegm-retained fluid formation were pointed out as pancreas and kidney. 3. Five physicians had different opinions regarding the classification of phlegm-retained fluid. 4. Warming and tonifing the spleen and stomach(溫補脾胃) and tonifing the kidney(補腎) were taken as the suitable methods for treating phlegm-retained fluid. The common characteristics of the Onbo School were verified in terms of formation and treatment methods for phlegm-retained fluid. However, specific common points were hardly found in other items. The Onbo School had varied opinions on the processing methods of Rehmannia glutinosa(熟地黃). Further discussion on related references are essential. KCI Citation Count: 1